Evaluation of the applicability of GARDskin to predict skin sensitizers in extracts from medical device materials - Jenvert, Rose-Marie; Larne, Olivia; Johansson, Angelica; Berglin, Mattias; Pedersen, Emma; Johansson, Henrik (Frontiers in Toxicology, 2024)
Biocompatibility testing of medical devices is governed by the ISO 10993 series of standards and includes evaluation of skin sensitization potential of the final product. A majority of all medical devices are tested using in vivo methods, largely due to the lack of in vitro methods validated within the applicability domain of solid materials.The GARDskin method for assessment of chemical skin sensitizers is a validated method included in the OECD Test Guideline 442E, based on evaluation of transcriptional patterns of an endpoint-specific genomic biomarker signature in a dendritic cell-like cell, following test chemical exposure. The current study aimed to evaluate the applicability of GARDskin for the purpose of testing solid materials by incorporation of extraction procedures described in ISO 10993-12:2021, as well as to demonstrate the functionality of the proposed protocols, by testing of custom-made materials spiked with sensitizing agents.It was shown that GARDskin is compatible with both polar and non-polar extraction vehicles frequently used for the purpose of medical device biological testing. Further, exploring three different material types spiked with up to four different sensitizing agents, as well as three unspiked control materials and commercial reference products, it was shown that the method correctly classified all evaluated test materials. Taken together, the data presented suggest that GARDskin may constitute a valid alternative to in vivo experimentation for the purpose of skin sensitization assessment of medical devices.